Non - Performing Loans in BRICS Nations : Determinants and Macroeconomic Impact - Syed, Aamir Aijaz; Tripathi, Ravindra (Indian Journal of Finance, 2019)
The issue of non - performing loans is considered as a serious threat towards the banking soundness of a country. Non - performing loans are those loans which cease to generate principal and interest and create a negative impact on the performance of banks. There are a host of factors which affect non - performing loans, which include both banking and macroeconomic variables. This study attempted to study the impact of macroeconomic determinants on the non - performing loans of BRICS countries covering the period from 2000 - 2016. The BRICS bloc was considered for the study as various previous studies showed that trading blocs also get affected by inter country non - performing loans' issues. This study used dynamic panel data approach for analysis using the fully modified ordinary least square model (FMOLS) along with cointegration analysis, and for robustness checks, this model incorporated the fixed and random ordinary least square methods. The results showed that unemployment had a positive relation with non - performing loans; whereas, growth and financial soundness of a country had a negative relation with non - performing loans. Saving rate of households also had an inverse relation with non - performing loans and inflation rate also showed a negative relation with default loans.